2015
DOI: 10.2166/wh.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of microbial risk associated with greywater by disinfection processes for irrigation

Abstract: Greywater is one of the most important alternative sources for irrigation in arid and semi-arid countries. However, the health risk associated with the microbial contents of these waters limits their utilization. Many techniques have been developed and used to generate a high microbiological quality of greywater. The main problem in the treatment of greywater lies in the nature of pathogenic bacteria in terms of their ability to survive during/after the treatment process. The present review focused on the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 119 publications
0
19
0
4
Order By: Relevance
“…Due to their small size and ability to persist in the environment, physical removal processes can be less effective compared to bacteria and protozoa, necessitating a disinfection step for high levels of removal or inactivation. Although UV inactivation is a common method of virus inactivation, viruses generally require a higher dose of UV for inactivation compared to bacteria and protozoa, which, combined with an infectivity dose that can be orders of magnitude less than bacteria and protozoa, often makes them the focus of more stringent human health risk standards (Al-Gheethi et al, 2016;Asano, 2005;USEPA, 2012).…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…Due to their small size and ability to persist in the environment, physical removal processes can be less effective compared to bacteria and protozoa, necessitating a disinfection step for high levels of removal or inactivation. Although UV inactivation is a common method of virus inactivation, viruses generally require a higher dose of UV for inactivation compared to bacteria and protozoa, which, combined with an infectivity dose that can be orders of magnitude less than bacteria and protozoa, often makes them the focus of more stringent human health risk standards (Al-Gheethi et al, 2016;Asano, 2005;USEPA, 2012).…”
Section: Microbiological Parametersmentioning
confidence: 99%
“…However, the impact on health due to the presence of microbial diversity becomes its limitation in utilization of greywater. The microbial load of the greywater has been investigated and reported extensively by many authors in the literature [1]. It has been reported that greywater have E .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing development in countries with high populations is associated with several impacts on the environment resulting from human waste. A common impact that has adverse effects on the environment is graywater, which is defined as any wastewater (other than black water) generated from domestic activities such as washing dishes, washing, and bathing (Al‐Gheethi et al 2015, Mohamed et al 2013 a, Al‐Mashaqbeh et al 2012, Anda et al 2010, Schäfer et al 2006, WHO 2006). Graywater represents the greatest potential source of domestic water storage in dwellings, accounting for as much as 50‐80% of total water use.…”
mentioning
confidence: 99%
“…Many bacterial species such as Bacillus sp., E.coli, Enterococci, S. aureus , and P. aeruginosa have been detected in graywater (Bani‐Melhem et al 2015, Katukiza et al 2014, Santasmasas et al 2013, Winward et al 2008, Casanova et al 2001). Therefore, improvement in collecting and treating graywater is important for public and environmental health (Al‐Gheethi et al 2015, Bani‐Melhem et al 2015, Katukiza et al 2014).…”
mentioning
confidence: 99%